Bundle-move analysis in research article of science and technology: connecting lexical bundles and rhetorical move - Insani, Ina; Roselani, Ni Gusti Ayu (Program Studi Sastra Indonesia UIN Sunan Ampel Surabaya, 2023)
This research identifies lexical bundles which are connected to move analysis in research article of Science & Technology. The corpus-based analysis was used to acquire lexical bundles qualification of frequency and range. A number of bundles which were listed in the corpus were identified structurally and functionally using taxonomy approach by Biber et al., (2004). Further analysis was conducted to connect lexical bundles expression with rhetorical move. Connecting lexical bundles and move analysis in research articles aims to test whether lexical bundles can be used as move markers in academic discourse. The classification of move in a full-length research articles was adapted from Nwogu (1997). In the various structural and functional forms of bundles which are found in this study bring to the list of lexical bundles which indicate various move. The finding of this research is mainly supporting previous study where some bundles expressions have strong connection to rhetorical move in research article. Other finding shows that lexical bundles expressions could occur in more than one move. However, we found that not all of the bundles could express specific move (e.g. the value of the, the length of the, absorption process of the) and not all move is expressed by lexical bundles (move 8).